A General Evaluation of the Reasons for Medication Wastage: A University Hospital Example - Yasemin Aslan; Leyla Kanmaz Demir (Association of Nurse Managers, 2023)
Aim: In this study, it was aimed to evaluate the medication wastage and associated factors in a university hospital and to reveal the economic dimension of medication wastage. Method: The population of this descriptive study consisted of 834 medications that were wasted in a university hospital in Istanbul. Sample selection was not made in the study and the entire population was taken into consideration. The data were collected using Medication Wastage Forms and Medication Wastage Reports recorded by the Pharmacy Department. Descriptive statistics (frequency, percentage) were used in the analysis of the data. The World Health Organization Anatomical Therapeutic Chemical (ATC) Classification System was used to classify wasted medications. Results: The study results showed that medication wastage has been mostly caused by preparation-related reasons, treatment changes, and adverse drug reactions. It was determined that the wastage rate was higher in pediatric hematology, chemotherapy, and adult hematology units. It was determined that the total cost of medication wastage was 98,950.12 ₺ and 66.98% of this cost was preventable. According to the Anatomical, Therapeutic and Chemical (ATC) Classification System, 33.81% of the wasted medication was classified as antineoplastic and immunomodulating agents. Conclusion: In this study, it was determined that the amount and cost of medication wastage in the hospital were at a serious level. It was determined that wastage predominantly occurred in units with high-risk patient groups and that a large part of it was preventable. Hospital management needs to focus on preventable causes of waste in terms of the effective use of resources.